Male Infertility associated with a Novel Mutation in Carney Complex - Maja Dimitrovska; Dijana Plaseska-Karanfilska; Jean K. Gogusev; Tatjana Milenkovic; Gjorgji Bozhinovski; Cedomir Dimitrovski (Clinical Medicine Insights: Endocrinology and Diabetes)
Carney Complex (CNC) is a rare syndrome characterized by spotty skin pigmentation and multiple neoplasms, notably cardiac myxomas, schwannomas, and endocrine tumours. It is often inherited in an autosomal dominant manner with PRKAR1A gene mutations found in the majority of cases. Male infertility is established as part of the CNC phenotype and is largely associated with Large cell calcifying Sertoli cell tumours (LCCSCT). We describe a case of a 30-year-old male patient with Carney Complex, presenting with severe oligoasthenozoospermia and primary pigmented nodular adrenocortical disease (PPNAD). During follow-up consults, the severe oligozoospermia and impaired semen motility persisted and the patient was also diagnosed with a recurring cardiac myxoma and LCCSCT. Molecular testing identified a novel PRKAR1A mutation involving a deletion of exons 4 to 7. Our findings suggest this mutation causes PRKAR1A haploinsufficiency, which may be directly linked to male infertility, irrespective of the presence of testicular tumours. Accordingly, in male patients with CNC, detection of a PRKAR1A gene mutation may serve as a predictive marker for infertility. This case report illustrates the importance of early consideration and management of infertility in male patients diagnosed with CNC.